HIPI: A REVIEW ON HADOOP MAP REDUCE FRAMEWORK USING IMAGE PROCESSING IN BIGDATA - Vijayalakshmi, P.S; Gomathy, K; Kumuthini, C (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, Big data is growing vey faster in the world. Big data is the large volume of data that consists of both structured and unstructured on a day-to-day basis. But it's not the amount of data. Big data is the data which includes sensor data, biometric data, Geo-spatial, Healthcare, power grid, transport, search engine and in Social networks. Hadoop process large amounts of data, in parallel, clusters of commodity hardware in a reliable and fault-tolerant manner. In this paper we review the Image processing using Map reduce technique with the help of HIPI (the image processing Tool).